Practicality Of Adobe Falash-Based Learning Media Sciebce Subjects - Sukri Katili; Supartin Supartin (PEDAGOGIKA, 2026)
The purpose of this study is to analyze the practicality level of Adobe Flash-based learning media in Natural Sciences and Social Sciences subjects. This study was conducted at SD Negeri 11 Kabila, using a third-grade research sample and simple random sampling. This type of research is included in the type of Research and Development (R&D) research by adopting the ADDIE development model. Testing the practicality level was carried out at the implementation stage. The results showed that the average percentage of implementation of Adobe Flash-based learning media showed that four meetings reached 100% with the criteria of "very good". While 93% of students gave a positive response to Adobe Flash-based learning media. It can be concluded that Adobe Flash-based learning media can be used in learning Natural Sciences and Social Sciences subjects